2020
DOI: 10.1186/s13058-020-01327-1
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in 21-gene recurrence scores between paired breast cancer samples is inversely associated with patient age

Abstract: Background: The Oncotype DX 21-gene Recurrence Score is a genomic-based algorithm that guides adjuvant chemotherapy treatment decisions for women with early-stage, oestrogen receptor (ER)-positive breast cancer. However, there are age-related differences in chemotherapy benefit for women with intermediate Oncotype DX Recurrence Scores that are not well understood. Menstrual cycling in younger women is associated with hormonal fluctuations that might affect the expression of genomic predictive biomarkers and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…There is very little previous work examining the effect of menstrual cycle on gene expression-based prognostic signatures, such as RS, ROR and EP, which are widely used in ER-positive breast cancer to estimate the risk of distant recurrence for patients receiving endocrine therapy and help guide the use of adjuvant chemotherapy. A recent study by Bernhardt et al [ 28 ] in 25 women reported a higher discordance of RS score when measured in paired samples from the 16 women < 50 years of age. Eight of the 16 cases < 50 years showed differences of > 4 U in the recurrence score between the paired biopsy compared with none of the 9 cases from older women.…”
Section: Discussionmentioning
confidence: 97%
“…There is very little previous work examining the effect of menstrual cycle on gene expression-based prognostic signatures, such as RS, ROR and EP, which are widely used in ER-positive breast cancer to estimate the risk of distant recurrence for patients receiving endocrine therapy and help guide the use of adjuvant chemotherapy. A recent study by Bernhardt et al [ 28 ] in 25 women reported a higher discordance of RS score when measured in paired samples from the 16 women < 50 years of age. Eight of the 16 cases < 50 years showed differences of > 4 U in the recurrence score between the paired biopsy compared with none of the 9 cases from older women.…”
Section: Discussionmentioning
confidence: 97%
“…Recent data from Bernhardt et al. suggests there may be discrepancies between RS values on core biopsy and resected tumour specimens, albeit impacted by patient age [ 59 ]. Patient data from two separate cohorts (both Ueno et al.)…”
Section: Discussionmentioning
confidence: 99%
“…While this analysis suggests that NET prescription following RS may be reasonable in tumour downstaging, 90% of cancers had T1/T2 disease limiting conclusions which may be drawn in relation to downstaging T3 or locally advanced disease. Recent data from Bernhardt et al suggests there may be discrepancies between RS values on core biopsy and resected tumour specimens, albeit impacted by patient age [59].…”
Section: Limitationsmentioning
confidence: 99%
“…Despite breast cancer subtype classification being based on the fairly ubiquitous presence of hormone receptors (ER, PR); the presence of ligands are somewhat overlooked. The relevance of age-related endocrine changes in driving transcriptomic and proteomic alterations in breast cancer has recently garnered attention, particularly with regards the robustness of biomarker assessment platforms such as OncotypeDX (47,48). This is a burgeoning area of research and it is clear that inclusion of the patient endocrine landscape may enhance robustness in the application of biomarkerbased algorithms (47).…”
Section: Discussionmentioning
confidence: 99%